Across the Board: Regina Palkovits. Issue 5 (30th January 2015) - Palkovits, Regina
Abstract In this series of articles, the board members of ChemSusChem discuss recent research that they consider of exceptional quality and importance for sustainability. In this contribution, Prof. Regina Palkovits describes some recent advances in heterogeneous catalytic transformations of lignocellulosic feedstocks into biofuels. While the recent works she highlights are of great significance, challenges with regard to catalyst stability, the associated deactivation mechanisms, and designs for aqueous‐phase reactions remain.